2007
DOI: 10.1111/j.1469-8137.2007.02222.x
|View full text |Cite
|
Sign up to set email alerts
|

Timing of bud set in Picea abies is regulated by a memory of temperature during zygotic and somatic embryogenesis

Abstract: Summary• It has been shown previously that height growth and bud phenology are influenced by the temperature during zygotic embryogenesis in Picea abies .• To test whether this phenomenon operates within individual plants, clones produced through somatic embryogenesis were used. Seeds were from a full-sib family produced in both a cold (outdoor) and a warm (inside a glasshouse) environment. Embryogenic clones derived from mature zygotic embryos from both crossing environments were cultured at 18, 23 and 28 ° C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
111
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 143 publications
(118 citation statements)
references
References 45 publications
5
111
1
1
Order By: Relevance
“…However, these differences were only observed between EMs proliferated at 23ºC in a culture medium containing 3.5 g/L agar (860 somatic embryos per gram of EM) and those proliferated at 28ºC with 3.5 g/L agar (1212 somatic embryos per gram of EM). Our results are in agreement with results obtained by Kvaalen & Johnsen (2008) in Picea abies, and opposite to findings reported by García-Mendiguren et al (2016) in P. radiata where they did not find differences among proliferation treatments for somatic embryo production. Furthermore, different environmental conditions at initiation stage of P. halepensis SE, did not lead to significant differences in the number of somatic embryos obtained (Pereira et al, 2016).…”
Section: Resultscontrasting
confidence: 52%
See 1 more Smart Citation
“…However, these differences were only observed between EMs proliferated at 23ºC in a culture medium containing 3.5 g/L agar (860 somatic embryos per gram of EM) and those proliferated at 28ºC with 3.5 g/L agar (1212 somatic embryos per gram of EM). Our results are in agreement with results obtained by Kvaalen & Johnsen (2008) in Picea abies, and opposite to findings reported by García-Mendiguren et al (2016) in P. radiata where they did not find differences among proliferation treatments for somatic embryo production. Furthermore, different environmental conditions at initiation stage of P. halepensis SE, did not lead to significant differences in the number of somatic embryos obtained (Pereira et al, 2016).…”
Section: Resultscontrasting
confidence: 52%
“…However, few studies have focused on the impact of temperature (Kvaalen & Johnsen, 2008), and the effect of different concentrations of agar in the culture medium has been studied mostly at maturation stage (Teyssier et al, 2011;Morel et al, 2014). In this sense, in our laboratory García-Mendiguren et al (2016) described in Pinus radiata (D. Don) that different temperatures and water availability conditions at initiation affected subsequent phases of SE; however, this effect on subsequent phases of the process disappeared when different environmental conditions were applied at proliferation.…”
Section: Introductionmentioning
confidence: 81%
“…Provenances did not group phylogeographically along the east-western major axis of the species range, but ecologically along a latitudinal/altitudinal gradient, similar to findings in P. canariensis (López et al, 2007) or P. contorta (Chuine et al, 2006). There is also a certain parallelism to the effects of epigenetic memory of cold and warm embryo formation described in other conifers, which are interpreted as a mechanism of adaptative phenotypic plasticity that improves the fitness of the same genotype in different environments (Besnard et al, 2008;Kvaalen and Johnsen, 2008;Søgaard et al, 2008). Against this background one might wonder whether, and to what degree, those moderate differences found between the studied stone pine provenances, distinguishable only after major spatial adjustments (that reflect a common, very stable microsite response of each and every genotype), might also be due to an epigenetic acclimatisation (Vendramin et al, 2008).…”
Section: Discussionmentioning
confidence: 61%
“…Some authors (Beuker et al 1998;Kvaalen, Johnsen 2008) also observed that provenance responses to a photoperiod are more pronounced than to temperature. This means a more important relation between growth and latitude than with temperature, which was also confirmed by our results.…”
Section: Discussionmentioning
confidence: 96%